Wine microbiome: impact of vitivinicultural practices - Lopes, Ana Cláudia Ferreira (2020)
Portugal is worldwide known for the quality and distinction of its wines and has been sharing a strong bond with the vitivinicultural sector since early days, with great economic impact. Several current problems, such as climate change and the scarcity of natural resources, have been affecting the agricultural sector, with winemaking exemplifying this. Aiming the overcome of those problems, several studies have been carried out in order to develop sustainable vitivinicultural practices, while preserving wine’s regionality and quality. One of the most researched subjects has been the terroir impact on wine’s organoleptic properties, and several studies have been reporting the influence of vine and wine’s microbiome, thus arising the importance of the microbial terroir. Therefore, there is a need to clarify the microbial terroir role on winemaking processes, identifying the microbial consortium and its evolution along the process, to understand their effect on the final product. Thus, a comparative study was developed, in which two grape varieties (Touriga Nacional and Aragonez) were produced simultaneously under two production modes (Organic and Integrated) and fermented by two different methods (spontaneous fermentation vs. commercial inoculation). Samples of Initial Must, Medium Fermentation and Final Fermentation were analysed by culture-dependent methods, molecular biology techniques and metagenomic tools, to evaluate the influence of vinicultural processes on microbiome and organoleptic properties of the 8 wines produced. This study demonstrated that the mode of production affects the diversity of initial must microbiome in both eukaryotes and prokaryotes. However, differences in the beginning of fermentation tend to decrease throughout the fermentation process. Regarding the fermentation method, in this study musts inoculated with the commercial yeast presented a lower biodiversity and a larger number of pathogenic microorganisms, unlike the musts resulting from spontaneous fermentation, which not only showed a higher biodiversity, but also exhibited a higher number of phytoprotective microorganisms.